Konseling Kelompok Pendekatan Rational Emotive Behavior Therapy (REBT) untuk Mereduksi Kecemasan Atlet Sebelum Bertanding - Larasati, Sectio Putri; Taufik, Taufik (Current Issues in Counseling, 2023)
Psychological disorders of anxiety in athletes become a threat to the achievement of athletes' achievements and careers. Anxiety in athletes is based on assumptions created by the athletes themselves. The irrational mindset of the athlete will threaten the moment before the game starts. In alleviating these conditions, group counseling is used through the Rational Emotive Behavior Therapy (REBT) approach which will help athletes to think logically for optimal self-realization. This paper uses literature studies and literature studies by exploring various studies according to competition anxiety in athletes and group counseling setting REBT in accordance with the ABCDE concept.